2013
DOI: 10.1111/2049-632x.12107
|View full text |Cite
|
Sign up to set email alerts
|

Draft genomes of 12 host-adapted and environmental isolates ofPseudomonas aeruginosaand their positions in the core genome phylogeny

Abstract: Pseudomonas aeruginosa is a Gram-negative opportunistic pathogen particularly associated with the inherited disease cystic fibrosis (CF). Pseudomonas aeruginosa is well known to have a large and adaptable genome that enables it to colonise a wide range of ecological niches. Here, we have used a comparative genomics approach to identify changes that occur during infection of the CF lung. We used the mucoid phenotype as an obvious marker of host adaptation and compared these genomes to analyse SNPs, indels and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

14
63
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(77 citation statements)
references
References 52 publications
14
63
0
Order By: Relevance
“…However, for those studies which do comment, isolates with unique sequence types comprise the majority of strains (Head and Yu 2004;Manos et al 2013). Rather than demonstrating a loss of motility based on infection status, I have shown that isolates from chronically infected patients, with a unique sequence type more closely resembled isolates from other clinical settings with moderate to high levels of positive motility reported.Similar to this study, a number of published studies have included non-CF and/or environmental isolates for comparison (Cullen et al 2015;Head and Yu 2004;Jeukens et al 2014; 119 Mahenthiralingam et al 1994;O'May et al 2006). Results from the current work are concordant with these earlier studies; both demonstrating enhanced motility among isolates arising from ecological niches outside of CF.…”
supporting
confidence: 86%
See 4 more Smart Citations
“…However, for those studies which do comment, isolates with unique sequence types comprise the majority of strains (Head and Yu 2004;Manos et al 2013). Rather than demonstrating a loss of motility based on infection status, I have shown that isolates from chronically infected patients, with a unique sequence type more closely resembled isolates from other clinical settings with moderate to high levels of positive motility reported.Similar to this study, a number of published studies have included non-CF and/or environmental isolates for comparison (Cullen et al 2015;Head and Yu 2004;Jeukens et al 2014; 119 Mahenthiralingam et al 1994;O'May et al 2006). Results from the current work are concordant with these earlier studies; both demonstrating enhanced motility among isolates arising from ecological niches outside of CF.…”
supporting
confidence: 86%
“…Typically, most studies have relied on using the PAO1 strain or knockout mutants as comparators (Carter et al 2010;Jeukens et al 2014; Jiricny et al 2014; Kukavica-Ibrulj et al 2008;Manos et al 2008;Manos et al 2013;O'May et al 2006;Yang et al 2011). While a standard needs to be included to account for inter-run variation and to set a baseline for isolate comparison, the expression and capabilities of this strain needs to be known in the context of the broader population so that degrees of change from this 37 baseline can be interpreted correctly.…”
Section: Quorum Sensingmentioning
confidence: 99%
See 3 more Smart Citations